(untitled) (Collaborate Engineering Daily Book Series, 2024)
This study provides a comprehensive analysis of Port Reception Facilities (PRFs) and their critical role in supporting compliance with MARPOL Annex V within the maritime industry from 2018 to 2023. The research employs a mixed-methods approach, integrating quantitative data on PRF operations with qualitative insights from stakeholder engagement. Key findings reveal significant advancements in environmental performance, including a 95% reduction in water pollutants, a 40% decrease in greenhouse gas emissions, and a 60% increase in solid waste recycling efficiency. The implementation of PRFs has achieved a compliance rate of 92% with MARPOL regulations and 88% with ISO standards. Furthermore, the study highlights a 30% increase in aquatic biodiversity and a 70% reduction in landfill volume associated with improved waste management practices. The integration of digital technologies has notably enhanced stakeholder engagement rates from 55% to 80%. Despite these positive outcomes, critical areas for future development are identified, including the need for continued investment in green technology, international standardization, and capacity building. These findings offer valuable insights for policymakers, port authorities, and industry stakeholders, contributing significantly to the existing literature on maritime environmental protection and sustainable port waste management strategies.